Buy My Trust, Before I Buy Your Food – Consumers’ Insights for Online Food Delivery Platforms During the COVID -19 Pandemic - Siddiqui, Aaliyah; Siddiqui, Mujahid (Indian Journal of Marketing, 2021)
Purpose : This study aimed to find the factors that affected the usage of OFD platforms during the emergent situation of the COVID-19 pandemic. Design/Methodology/Approach : The extended valence framework and UTUAT2 model were integrated to develop a parsimonious model comprising trust, perceived risk, performance expectancy, habit, and buying intention. The model was tested by employing structural equation modeling with a sample of 362 respondents from India. Findings : The relationship between trust and buying intention was found to be the strongest amongst all factors. All modeled predictors of trust were found to impact trust significantly, while perceived risk was found to have an inverse relation with trust. Research Limitations/Implications : The constructs presented in the model successfully explained the factors that impacted OFD platforms during the COVID-19 pandemic. The understanding of consumers’ responses developed in the study is a useful addition to the literature. Practical Implications : The study provides direction to promoters and marketers of OFD platforms to identify specific factors that can help boost the buyers’ intention to purchase during emergency situations. Originality/Value : The integration of two theoretical models: the extended valence framework and UTUAT2 is unique in the context of OFD platforms. The COVID-19 situation and circumstances therein provide a unique research situation for an improved understanding on the subject.